Implementasi Nilai-Nilai Moderasi Beragama Melalui Proyek Penguatan Profil Pelajar Rahmatan Lil’alamin dalam Bingkai Kebhinekaan - Habibi , Wildan; Qumiyatul Lailiyah , Binti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The Background of this research explains the context of Indonesia as a multicultural and multireligious country, where religious moderation is a key element in maintaining social harmony and peace. The application of religious moderation and diversity values at MAN 1 Nganjuk through the Rahmatan Lil ‘Alamin Student Profile Strengthening Project (P2RA) is one way to shape a moderate and tolerant generation. This research uses a qualitative approach. The focus of this research is on the implementation of the Rahmatan Lil ‘Alamin Student Profile Strengthening Project (P2RA) and the impact it has on 11th-grade students at MAN 1 Nganjuk. The research results show the implementation stage, project activities begin to be implemented according to plan, with implementation carried out in an integrated and collaborative manner by educators. The final stage of PPRA is evaluation. This evaluation includes an attitude assessment by measuring the achievement of Rahmatan Lil'Alamin Student's character and diversity which is categorized into several levels: MB (starting to develop), B (developing), BSH (developing according to expectations), and SB (very developing). Reflection is carried out to review successes, shortcomings and obstacles faced for future improvements